Review of the landscape aesthetic potential research in Lithuania / Kraštovaizdžio estetinio potencialo tyrimų lietuvoje apžvalga - Dovilė Kalkė (Mokslas: Lietuvos Ateitis, 2014)
The article is an overview of the first manifestations of landscape aesthetic assessment, subsequent research and its development in Lithuania. It analyzes the first methodologies in Lithuania for  assessment of landscape aesthetic resources, insights by different authors into the compositional structure of landscape architecture, development of aesthetic-psychological assessment and others aspects, which may be important to research of aesthetic potential of a landscape. Most important researches are reviewed in the chronological order by naming their essential distinctive features, in order to evaluate the development of landscape aesthetic assessment up to the present day.